Initial perception of junior high students on ethnomathematics-based online learning during the COVID-19 pandemic - Rona Happy Mumpuni; Marsigit Marsigit (International Journal of Evaluation and Research in Education (IJERE), 2022)
This research aimed to determine the students' initial perception in Islamic-based junior high school and Madrasah Tsanawiyah (MTs) in Yogyakarta toward ethnomathematics-based online learning during the COVID-19 pandemic in 2020. The descriptive quantitative method was employed through a questionnaire for data collection followed by descriptive statistical analysis. The research population were 600 junior high students and MTs in Yogyakarta. The instrument was validated by expert judgment and proved reliable as research means with Cronbach’s Alpha coefficient of 0.873. Results indicated students' perception in several categories: strongly positive by 7% or 42 students, positive by 23% or 138 students, moderate by 40.67% or 244 students, negative by 24% or 144 students, and strongly negative by 5.33% or 32 students. The general conclusion was that junior high and MTs students in Yogyakarta had moderate initial perception toward ethnomathematics-based online learning during the COVID-19 pandemic.